Chlorella vulgaris enhance the photodegradation of chlortetracycline in aqueous solution via extracellular organic matters (EOMs): Role of triplet state EOMs. (1st February 2019) - Tian, Yajun; Zou, Jinru; Feng, Li; Zhang, Liqiu; Liu, Yongze
Abstract: Algae, which are ubiquitous in surface waters (e.g., lakes, ponds, wetlands) may play an important role in sunlight-driven transformation of compounds. This study is to investigate the role of algae (Chlorella Vulgaris) in chlortetracycline (CTC) photolysis and explore the photosensitive mechanism. The algae were found to significantly accelerate the photodegradation rate of CTC and extracellular organic matters (EOMs) were confirmed to be the major active substances. Triplet state EOMs ( 3 EOMs*) were verified to be the dominant reactive species with 93% contribution to the indirect photodegradation rate of CTC, while ·OH and 1 O2 contributed minor (7%). The steady-state concentration of 3 EOMs* was determined by probe compounds (2, 4, 6-trimethylphenol) to be 3.50 × 10 −14 –1.88 × 10 −13  M with the increase of EOMs from 2.0 to 8.0 mg L −1 . The rate constant for reaction of 3 EOMs* with CTC was calculated to be 3.17 × 10 9  M −1 s −1 . 3 EOMs* were found to react with CTC mainly via electron transfer, on basis of susceptible reaction of 3 EOMs* with the hydroxyl and amidogen groups in CTC. In addition, the energy transfer of 3 EOMs* to CTC was possible according to the higher energy of 3 EOMs* than that of triplet CTC. Graphical abstract: Image 1 Highlights: Chlorella Vulgaris could significantly accelerate the rate of CTC photolysis. Algogenic EOMs were determined to be the dominant photosensitizer. Triplet state EOMs ( 3 EOMs*) contributed 93% to indirect photolysis of CTC. 3 EOMs* reacted with CTC mainly via electron transfer and energy transfer.